Do Malaysian school students like learning accounting through integration of ICT into the teaching and learning process? - Tan, Boon See; Salleh, Arfah; Wong, Su Luan; Abu Bakar, Kamariah (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
This paper explores the Malaysian school students' receptiveness and factors towards learning the subject of Principles of Accounting (Prinsip Perakaunan) at SPM Level through integration of ICT into the teaching and learning process. A total of 150 Academic and Technical National Secondary Schools nationwide participated in the research conducted by the Ministry of Education, Malaysia. To facilitate the teaching and learning process under the new ICT-based environment, copies of a Lesson Plan Guidebook for the subject which propose an ICT-based pedagogical approach were distributed to the accounting teachers. A qualitative study to assess 238 students' perceptions on their understanding of the subject contents and interest was conducted through structured open-ended questions. The results show students' understanding level was moderate. However, the majority of students were interested in this novel approach. The content analysis reveals the external and internal dimension of factors which influence differences of perceptions. The external dimension contains factors of teaching competency and course material; whereas, internal dimension is attributed to student's prior knowledge and experience which give impact to the learning process. Respondents who showed unfavourable perceptions expressed the insufficiency of notes and exercises provided in the educational accounting software, and lack of effective teaching. In addition, the individual's level of computer proficiency, academic foundation, and family background could not be neglected as factors contributed to the negative perceptions. Those who exhibited favourable perceptions also found integration of ICT enlightening and expedited the learning process as well as cultivating them to master some generic skills.